Pseudoporphyria and nonsteroidal antiinflammatory agents in children with juvenile idiopathic arthritis. - De Silva, B; Banney, L; Uttley, W; Luqmani, R; Schofield, O (2000)
Pseudoporphyria is characterized by erythema, blistering, and scarring on sun-exposed skin. Nonsteroidal antiinflammatory drugs (NSAIDs) are implicated in the etiology of this condition. In a 1-year prospective study of children attending the pediatric rheumatology clinic in Edinburgh we found a prevalence of pseudoporphyria of 10.9% in children taking NSAIDs for juvenile idiopathic arthritis. Naproxen was the most commonly implicated NSAID, independent of dosage. Blue/gray eye color was an independent risk factor for the development of pseudoporphyria. We would advise caution in prescribing naproxen in these children to prevent disfiguring facial scarring.